2018
DOI: 10.21059/buletinpeternak.v42i2.31767
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activity and Malondialdehyde Concentration on Broiler Fed Contain Lauric Acid and Areca vestiaria Giseke

Abstract: The objective of the study was to determine antioxidant enzyme activity and concentration of malondialdehyde on broiler which consumed feed containing lauric acid and natural antioxidant from Areca vestiaria Giseke. The study used 240 day-old chicks of Lohmann MB 202 P strain placed randomly at 24 experimental cage units (10 chickens each) of the litter system. The average temperature of the cage at the study was 25.80 to 32.08 0 C with relative air humidity rate of 67.69 to 86.20%. The research method followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Spleen weight was significantly increased by alpha-monolaurin; however, other organ weights were not affected. These results agree with London, Manalu, and Wiryawan [13], who found that the lauric acid source did not influence the dressing percentages (carcass, muscle, and abdominal fat weights) of chickens. Our results disagree with Liu et al [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Spleen weight was significantly increased by alpha-monolaurin; however, other organ weights were not affected. These results agree with London, Manalu, and Wiryawan [13], who found that the lauric acid source did not influence the dressing percentages (carcass, muscle, and abdominal fat weights) of chickens. Our results disagree with Liu et al [37].…”
Section: Discussionsupporting
confidence: 91%
“…The increase in muscle unsaturated fatty acid content (oleic and linolenic fatty acids) may be due to decreased lipid peroxidation [46][47][48][49][50][51]. Moreover, Londok, Sumiati, Wiryawan, and Manalu [13] found that unsaturated fatty acids were increased by lauric acid supplementation in broiler diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats supplemented with LA diets showed a healthy GIT morphology with an increase in the mucous membrane, longer villi, shorter crypt, increased phospholipid/ protein ratio of jejunal mucous lipids, and enhanced membranebound enzyme activity (Takase et al, 1990). Spleen was significantly increased in weight by monolaurin; but other organ weights were not affected as reported in (Londok et al, 2018). The enhancement in the leg and breast muscles by supplementation with LA and monolaurin was linked with increased protein deposition in broilers, as total protein in serum was significantly increased.…”
Section: Discussionmentioning
confidence: 73%